Estimasi Biaya Pembangunan Rumah Sederhana Dengan Metode Komparasi Rangka Atap Kayu Vs Baja Ringan (Studi Kasus: Luwu) - Putri Rahayu; Anggel Erpa Erong Pakiding (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
With advancements in construction technology and the increasing scarcity of high-quality timber, selecting alternative materials for building roof trusses has become crucial. The scarcity of timber has made it difficult to procure and relatively expensive, leading to the widespread adoption of cold-formed steel (light-gauge steel) as a substitute. This study aims to analyze cost estimates and construction time efficiency for roof truss structures in simple residential buildings by comparing timber and cold-formed steel in the Luwu Regency area. The research employs a quantitative comparative approach, calculating work volumes based on the geometric specifications of a case study model, analyzing labor productivity, and compiling a Budget Plan (RAB) that specifically references the latest (2026) Unit Price Analysis (AHSP) indices and Indonesian National Standard (SNI) loading standards. The comparative results indicate that, in terms of structural strength and tensile quality, cold-formed steel exhibits more uniform and consistent performance than timber. Economically, although cold-formed steel may require additional bracing in large-span structures due to lower flexural rigidity, the total installation cost for roof trusses in standard residential buildings is lower and more economical than that of timber. Furthermore, regarding time efficiency, the installation of cold-formed steel roof trusses is significantly faster and requires less labor than conventional timber trusses. The use of cold-formed steel also offers technical advantages, such as termite resistance and non-flammability, while being more environmentally friendly by supporting forest conservation.